HIGHWAY AND RAILWAY CROSSING MANAGEMENT MODEL TO IMPROVE SIDOARJO-TARIK CROSSING SAFETY (COMPARISON BETWEEN INDONESIA AND MALAYSIA) - Supriyatno, Dadang; Syaiful, Syaiful; Wiwoho Mudjanarko, Sri; Wardhani, Asri Kusuma (Journal of Applied Engineering Science, 2025)
The railway level crossings between Sidoarjo-Tarik in Sidoarjo Regency are mostly railway crossings without barriers that are prone to traffic accidents due to conflicts at railway crossings between road users and passing trains, which have the potential to cause accidents. This study aims to provide recommendations for handling in accordance with regulations on improving the safety of railway crossings between railways and roads and guidelines on technical guidelines for railway crossings between roads and railways. The survey conducted in this study was a road inventory to determine the geometry of railway level crossings and a survey of road user behavior to determine the behavior of road users crossing railway. Recommendations for handling the railway crossings between Sidoarjo-Tarik in Sidoarjo Regency that are appropriate to improve safety and prevent accidents are to install barriers and close category 2 to 4meters of crossings.